Poverty Stoplight - povertystoplight.org (2018)
What is the Poverty Stoplight? The Stoplight is a tool that seeks to a ctivate the potential of families and communities to lift themselves o ut of poverty. Using a technology platform, it offers a self-assessmen t survey and intervention model that enables people to develop practic al solutions to overcome their specific needs. We work with organizati ons from different sectors around the world and bring together a netwo rk of powerful actors with one clear mission: eliminate poverty worldw ide. The Stoplight Community is comprised of government agencies, priv ate companies, small and medium-sized enterprises, non-profits, cooper atives, microfinance organizations, academic institutions, and sports clubs, among others.